Targeting childhood, adolescent and young adult non‐Hodgkin lymphoma: therapeutic horizons. (27th March 2016) - Galardy, Paul J.; Bedekovics, Tibor; Hermiston, Michelle L.
Summary: Non‐Hodgkin lymphoma (NHL) is the third most common malignancy in children, adolescents and young adults (CAYA). NHL is a diverse set of diseases that arise at key regulatory checkpoints during B or T cell development in the bone marrow, germinal centre or thymus. While advances in the use of conventional cytotoxic agents have led to dramatic improvements in survival, these cures are associated with significant acute and long‐term toxicities. Moreover, the prognosis for CAYA patients with relapsed or refractory NHL remains dismal, with the vast majority dying of their disease. Thanks to a large number of candidate‐based biological studies, together with large‐scale sequencing efforts, there has been an explosion of knowledge regarding the molecular pathophysiology of B‐ and T‐NHL. This has ushered development of a flurry of novel therapeutic approaches that may simultaneously provide new hope for relapsed patients and an opportunity to reduce the therapeutic burden in newly diagnosed CAYA. Here we review a selection of the most promising new therapeutic approaches to these diseases. While the vast majority of these agents are untested in children, on‐going work from many cooperative groups will soon explore their use in paediatric disease, in hope of further improving outcomes while maximizing quality of life.